2016
DOI: 10.1016/j.freeradbiomed.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The circadian gene Rev-erbα improves cellular bioenergetics and provides preconditioning for protection against oxidative stress

Abstract: Diurnal oscillations in the expression of antioxidant genes imply that protection against oxidative stress is circadian-gated. We hypothesized that stabilization of the core circadian gene Rev-erbα (Nr1d1) improves cellular bioenergetics and protects against nutrient deprivation and oxidative stress. Compared to WT, mouse lung fibroblasts (MLG) stably transfected with a degradation resistant Rev-erbα (Ser55/59 to Asp; hence referred to as SD) had 40% higher protein content, 1.5-fold higher mitochondrial area (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 66 publications
2
37
1
1
Order By: Relevance
“…Moreover, the level of ROS decreased with SR9009 treatment in a concentration‐dependent manner; this effect was accompanied by down‐regulation of the NADPH oxidases gp91phox, p47phox, p40phox, and p22phox. This finding is in agreement with a previous study showing that REV‐ERBα protected cells from oxidative stress (14). Gp91phox, p67phox, p47phox, p40phox, and p22phox are important regulatory subunits of the ROS system (33).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, the level of ROS decreased with SR9009 treatment in a concentration‐dependent manner; this effect was accompanied by down‐regulation of the NADPH oxidases gp91phox, p47phox, p40phox, and p22phox. This finding is in agreement with a previous study showing that REV‐ERBα protected cells from oxidative stress (14). Gp91phox, p67phox, p47phox, p40phox, and p22phox are important regulatory subunits of the ROS system (33).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the skeletal muscle of NR1D1 knockout mice displayed reduced mitochondrial content and oxidative function (13). According to Sengupta et al (14), REV‐ERBα also protects cells against oxygen stress. Mouse lung fibroblasts transfected with a degradation‐resistant REV‐ERBα [Ser (55/59) to Asp, SD] showed a 4‐fold reduction in mitophagy.…”
mentioning
confidence: 99%
“…Sengupta and colleagues demonstrated that NR1D1 controls cellular homeostasis and reduces oxidative stress. Also, embryonic fibroblasts from C57Bl/6-SD transgenic mice showed increased mRNA levels of the downstream antioxidants HO-1, Mn superoxide dismutase, and catalase compared with wild-type mice 31 . Furthermore, Woldt and co-workers reported that NR1D1 deficiency in skeletal muscle resulted in reduced mitochondrial content and oxidative activity, whereas its overexpression in muscle or pharmacological activation in vivo increased exercise capacity 12 .…”
Section: Discussionmentioning
confidence: 93%
“…A study in athletes found that plasma levels of glutathione and catalase are higher in the evening compared to the morning, suggesting higher capacity to cope with oxidative stress ( Ammar et al 2015 ). Mechanistic studies in mouse MEFs revealed increased catalase levels upon constitutive overexpression of Reverba , suggesting a direct link to the molecular clock ( Sengupta et al 2016 ). In a study of mouse liver, glutathione expression was rhythmic and peaked at the beginning of the active phase ( Xu et al .…”
Section: Mitochondrial Redox Homeostasis and The Circadian Clockmentioning
confidence: 99%